Hydraulic Rebar Cutter (International Journal of Current Engineering and Technology, 2015)
In the work of liberalization (more freedom in action) the civil & mechanical sector has taken much importance in advancement & technology in various fields, and also much than the core industrial sector. In most developed cities need a lot of man power to split bar in to small parts. This man power requires various equipment viz. Hammer, chisel, hacksaw etc. Thus in order to avoid these project benefits in various ways. Use this lightweight tool to cut steel bars and other materials anywhere. Hydraulic power means minimum operator effort and a smooth guillotine-action reduces the risk of jamming Double-acting operation Cutting range 8 to14 mm in stroke. Hydraulic fluids also called hydraulic liquids are the medium by which power is transferred in hydraulic ma-chinery. The hydraulic fluid also known as tractor fluid, hydraulic fluid is the life of the hydraulic circuit. It is usually petroleum oil with various additives. Some hydraulic machines require fire resistant fluids, depending on their applications. In some factories where food is prepared, either an edible oil or water is used as working fluid for health and safety reasons. In addition to transferring energy, hydraulic fluids needs to lubricate components, suspend contaminants and metal filling for transport to the filter and to function well to several hundred degree Fahrenheit or Celsius.
Keywords: Hydraulics; Valves; Hoses; Hydraulic power pack; Hydraulic bar cutter; Cutting Tool, etc.